Implementing Sure Start Policy Context, Networks and Discretion - Song, Xiongwei (Springer Singapore, 2018)
In 1997, the Labour Government came to power in the UK and committed to reforming public service delivery, particularly towards the improvement of children's services. This book analyses Labour Party's subsequent strategy towards public service delivery emphasising, on one level, devolving more power to frontline deliverers, while on the other, strengthening central control through a variety of means, leading to a 'mixed-approach' in its overall reforms. The book focuses on the implementation process involved in rolling out its Sure Start policy in order to understand and analyse the dynamics in Labour's approach to delivery. In so-doing, it draws on implementation and policy network theories to offer an original analytical framework - 'the implementation network approach' - to explain the implementation process of Sure Start policy. This book will be undoubtedly appealing to the students and scholars engaged in the fields of Public Policy and British Politics.